0
$\begingroup$

I have a problem that asks a few questions on the probability of two events where P(A) = 0.6, P(B) = 0.7, and $P(A \cap B)$ = 0.4

i.) The first question asks to calculate the probability of P(A'|B).

Since $$P(A | B) = \frac{P(A \cap B)}{P(B)}$$

My solution was to do $$P(A' | B) = \frac{P(A' \cap B)}{P(B)} = \frac{(0.4) (0.7)}{0.7} = 0.4$$

However, the answer appeared to be: $$P(A' | B) = \frac{0.4}{0.7} = 0.5714$$

ii.) The second asks to calculate the probability of P(A'|B').

My solution was to do $$P(A'| B') = \frac{P(A' \cap B')}{P(B')} = \frac{(0.4) (0.3)}{0.3} = 0.4$$

However, the answer appeared to be: $$P(A'| B') = \frac{0.1}{0.3} = 0.3333$$

I was wondering if anyone can help me see where I went wrong here with both of these questions, or if I'm misunderstanding the actual formulas and how to use them.

$\endgroup$
  • 3
    $\begingroup$ If $A$ and $B$ are not independent events, $P(A\cap B)\neq P(A)P(B)$. $\endgroup$ – Zhuoran He Oct 19 '17 at 1:06
  • $\begingroup$ Yeah, I found out that they weren't. Does that mean I'd have to use a Venn Diagram to find the correct solutions as I can no longer use that formula? $\endgroup$ – Broadsword93 Oct 19 '17 at 1:09
  • 2
    $\begingroup$ Yes. Venn diagram is the right way to follow. $\endgroup$ – Zhuoran He Oct 19 '17 at 1:10
  • $\begingroup$ More formally inclusion-exclusion or law of total probability is how you might describe the process without venn diagrams. Note for example that $Pr(B)=Pr(A\cap B)+Pr(A'\cap B)$. You know $Pr(B)$ and $Pr(A\cap B)$ from the problem statement. $\endgroup$ – JMoravitz Oct 19 '17 at 1:17
1
$\begingroup$

Your task is to use the algebra of sets and rules of probability to express what you seek in terms of the three probabilities that were provided: $\mathsf P(A\cap B)=0.4, \mathsf P(A)=0.6,$ and $\mathsf P(B)=0.7$.

Also clearly $\mathsf P(A\cap B)\neq \mathsf P(A)\,\mathsf P(B)$, so the events are not independent.

Use that $\qquad\mathsf P(A'\cap B) ~{= \mathsf P(B\smallsetminus (B\cap A)) \\ = \mathsf P(B)-\mathsf P(A\cap B)}$

Likewise that $\mathsf P(A'\cap B') ~{= 1-\mathsf P(A\cup B)\\ = 1- \mathsf P(A)-\mathsf P(B)+\mathsf P(A\cap B)}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.